Influence of marital expectations on marital dissatisfaction among adult and Non-formal education learners in Sokoto Metropolis, Sokoto State, Nigeria - Yusuf, Murtala Akanbi; Alkali, Muhammad (Electronic Journal of Education, Social Economics and Technology, 2022)
The study examined the influence of marital expectations on marital dissatisfaction among Non-formal education learners who are divorces in Women Continuing Education Centre Sokoto, Sokoto state, Nigeria. The population of this study was all 579 divorcees in Women Continuing Education Centre, Sokoto and a sample size of 354 divorcees consented to participate in the study. The researchers used Marital Dissatisfaction Scale (MDS), Factors for Marital Dissatisfaction Questionnaire (FMDQ) and Shukla Comprehensive Marital Expectation Scale (SCMES). The research questions were answered with use of frequency and percentages and the hypothesis was tested using t-test of independent sample. The findings revealed majority of the couples that were studied were highly dissatisfied with their marital lives hence sought for divorce. And marital dissatisfaction happens when marital expectations do not forthcoming as couples with high marital expectations were significantly dissatisfied with their marital lives than couples with low marital expectations. The study recommended that Non-formal Education premarital counselling should be organized for prospective couples to have less marital expectations and be positive about marriage this programme will reduce tension when marital expectations are not forthcoming as taught.